FUNDAMENTE ŞI STRATEGII DE VALORIFICARE A RELAŢIEI ŞCOALĂ-FAMILIE-COMUNITATE ÎN CONTEXTUL FORMĂRII IMAGINII INSTITUŢIEI DE ÎNVĂŢĂMÂNT ÎN MEDIUL RURAL - USM ADMIN (Moldova State University, 2010)
Research shows a theoretical and applied study on educational institutions image in rural areas in terms of school - family - community partnership. Here are reflected the directions for the optimization of educational process, operating con- ditions in the educational institution and the main features of rural environment. There are analyzed the results of a survey of opinions and the implications of image recovery training of educational institution in partnership with social actors.